Clinicopathological characteristics and gene mutations in 11 patients with lipoprotein glomerulopathy - Yan Qin; Xiao-Jing Sun; Yi-Fang Hu; Meng Jing; Xiao-Juan Yu; Ming-Hui Zhao; Ying Tan (Renal Failure)
Objective Lipoprotein glomerulopathy (LPG) is a rare disorder characterized by the development of glomerular lipoprotein thrombosis. LPG exhibits familial aggregation, with mutations in the apolipoprotein E (APOE) gene identified as the leading cause of this disease. This study aimed to investigate APOE gene mutations and the clinicopathological features in eleven LPG patients.Methods Clinicopathological and follow-up data were obtained by extracting DNA, followed by APOE coding region sequencing analysis. This study analyzed clinical and pathological manifestations, gene mutations, treatment and prognosis.Results The mean age of the eleven patients was 33.82 years. Among them, five had a positive family history for LPG, ten presented with proteinuria, four exhibited nephrotic syndrome, and six presented with microscopic hematuria. Dyslipidemia was identified in ten patients. In all renal specimens, there was evident dilation of glomerular capillary lumens containing lipoprotein thrombi, and positive oil red O staining was observed in frozen sections of all samples. APOE gene testing revealed that one patient had no mutations, while the remaining ten patients exhibited mutations in the APOE gene, with three patients presenting with multiple mutations simultaneously. Following the confirmation of LPG diagnosis, treatment with angiotensin-converting enzyme inhibitor (ACEI)/angiotensin receptor blocker (ARB) was initiated, and the disease progressed slowly.Conclusion LPG is histologically characterized by lamellated lipoprotein thrombi in glomeruli, and kidney biopsy is essential for diagnosis. Mutations in the APOE gene are the leading cause of LPG. This study revealed clinicopathological characteristics and APOE gene mutations in patients with LPG, which helps us better understand the disease.